Precaution incentives in accident settings - Friehe, Tim (Gabler Edition Wissenschaft. Ökonomische Analyse des Rechts., 2008)
One central function of tort law is the inducement of precaution incentives. This is particularly welcome in settings in which the internalization of interdependencies between individuals relating to care and expected harm would otherwise not take effect due to high transaction costs broadly conceived, accident settings being a prime example. Tim Friehe analyzes important aspects for the design of tort law which intends to induce optimal individual choices and possible limitations of workable tort law in varied settings. Incentives to take precaution, which affect the accident probability and/or the magnitude of the harm in the event of an accident, are of primary interest in this context. After providing an extensive review of the literature relating to the economic analysis of tort law, the author goes on to discuss the consequences of victims with different harm levels. In particular, using average harm as a compensation measure in order to save administrative costs is considered and a scheme to make the revelation of the individual harm level incentive-compatible is devised. Furthermore, the book contributes to the ongoing discussion on the effects of judgment proofness and the distinction between unilateral harm and bilateral harm accidents. Finally, the author highlights the consequences of the consideration of hitherto neglected behavioral dimensions for the conclusions of the economic analysis of tort law.